Mechanical Properties and Fracture Surface Morphology of Quartz Sandstone Under Triaxial Shear - Zhinan LIN; Shihong FENG; Jiaquan WANG; Qiang ZHANG; Haifeng LONG (工程科学与技术)
To study the shear damage deformation characteristics of intact rock in rock slopes under three-dimensional compressive–shear stress conditions, 16 sets of triaxial shear tests were conducted on saturated intact fine-grained quartz sandstone with simple composition and homogeneous structure under different confining pressures by using the Rock Top–50HT full-stress multi-field coupling triaxial test system. In the tests, the corresponding triaxial shear stress–strain curves and the shear–failure fracture surfaces containing original rock debris were obtained, the nonlinear variations of the strength characteristics of quartz sandstone under triaxial shear stress were analyzed, and the triaxial shear failure mode and the roughness characteristics of the fracture-surface morphology of quartz sandstone were explored. Also, based on the Delaunay point–cloud discretization algorithm, the failure fracture surface of quartz sandstone was reconstructed, and the variation characteristics of its potential contact part with the effective inclination threshold of the surface were analyzed. The results show that with increasing normal stress, the triaxial shear failure mode of quartz sandstone changes gradually from brittle failure to plastic failure and finally to plastic flow failure. The triaxial shear strength of quartz sandstone shows obvious nonlinear variation with increasing confining pressure. The Mohr–Coulomb criterion is used to fit the triaxial shear strength of quartz sandstone via piecewise linear fitting, and it is found that with increasing confining pressure, the cohesion increases while the internal friction angle decreases. The three-dimensional roughness characteristics of the shear–failure fracture surface are evaluated using the traditional Grasselli model, and its nonlinear fitting parameters $θ _{{max}}^*$ and c fully describe the roughness characteristics of the fracture surface under triaxial shear failure. The present results are very important for predicting the triaxial shear strength of rock under complex stress and for evaluating the stability of slopes in rock engineering and optimizing the design schemes for supporting them.